THE PROBLEM OF FORMATION OF THE SPEECH CULTURE OF STUDENTS IN THE LESSONS OF LEARNING LITERATURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes the "Problem of the formation of the culture of students' speech." Three components of speech culture are revealed: normative, communicative and ethical. As a result of the disclosure of these components, it was shown that the culture of reading is the most important part of the general culture of a person.